2008
DOI: 10.1002/cncr.23750
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and molecular considerations for cancer risk

Abstract: Human papillomaviruses (HPVs) are a major cause of cancer globally, including cervical cancer. The HPV 'early' proteins, E6 and E7, are the chief oncoproteins involved in cancer progression. These oncoproteins are more highly expressed in high-grade dysplasias and invasive cancer coincident with reduced viral DNA replication and reduced production of infective progeny virions. The E6 and E7 oncoproteins interact with several cellular proteins-classically TP53 and RB1, respectively-leading to the degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 160 publications
1
56
1
1
Order By: Relevance
“…HPVs are currently believed to be the most common cause of cancers induced by an infectious agent (zur Hausen, 2006(zur Hausen, , 2009Whiteside et al, 2008). HPVs are a group of viruses of the Papillomaviridae family, which contain double-stranded circular DNA of B8 kb (Table 1) and use the host DNA machinery to replicate and proliferate.…”
Section: Human Papilloma Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…HPVs are currently believed to be the most common cause of cancers induced by an infectious agent (zur Hausen, 2006(zur Hausen, , 2009Whiteside et al, 2008). HPVs are a group of viruses of the Papillomaviridae family, which contain double-stranded circular DNA of B8 kb (Table 1) and use the host DNA machinery to replicate and proliferate.…”
Section: Human Papilloma Virusmentioning
confidence: 99%
“…Several recent studies have shown that E6 and E7 bind to different cell proteins involved in the processes of adhesion, apoptosis, cell cycle, DNA repair, metabolism, signal transduction, transcription and other functions (Horikawa and Barrett, 2003;Whiteside et al, 2008;Howie et al, 2009;McLaughlin-Drubin and Mu¨nger, 2009). In addition, deregulation of the expression of several miRNAs in the host cells associated with HPV infection induced by some of its oncoproteins has been noted by several authors (Martinez et al, 2008;Reshmi and Pillai, 2008;Wang et al, 2008Wang et al, , 2009.…”
Section: Human Papilloma Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, promoter hypermethylation of DAPK was investigated and found to be significant higher in high-risk HPV infected samples than low-risk HPV infected samples and non-HPV infected samples (p<0.0001). It is thought that some Oncogenic viruses are known to interact with, and to modulate the expression of DNA methyltransferases (DNMTs), resulting to in the transactivation and transrepression of both cellular and viral genes [23,24]. Even though the relationship between HPV and aberrant methylation in CC is not well understood, some reports suggested E6 and E7 oncoprotein of high-risk HPV increase the expression and activity of DNMT1, which is the major mammalian enzyme responsible for maintaining CpG methylation patterns in the cell following replication, through the suppression of TSG p53 [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The paradox is that, although infection with oncogenic types of HPV is very common, malignancy is a rare outcome. This difference in incidence between infection and cancer development reveals the significance of complex interactions between viral, environmental and host-related factors (Frazer, 2009;Moscicki et al, 2006;Snijders et al, 2006;Whiteside et al, 2008;zur Hausen, 2008). Viral persistence is an important determinant in this sequence of events, while immune status, viral integration into the host DNA, and infection with multiple HPV genotypes have significant roles.…”
Section: Vaginal Carcinomas 60-91%mentioning
confidence: 99%